Shared Care During Breast and Colorectal Cancer Treatment: Is It Associated With Patient-Reported Care Quality?. Issue 5 (September 2019) - Doose, Michelle; McGee-Avila, Jennifer; Stroup, Antoinette M.; Ferrante, Jeanne; Xu, Baichen; Herman, Natalia L.; Demissie, Kitaw; Tsui, Jennifer
Abstract : ABSTRACT: There is growing evidence that shared care, where the oncologist, primary care physician, and/or other specialty physicians jointly participate in care, can improve the quality of patients' cancer care. This cross-sectional study of breast and colorectal cancer patients ( N = 534) recruited from the New Jersey State Cancer Registry examined patient and health system factors associated with receipt of shared care during cancer treatment into the early survivorship phase. We also assessed whether shared care was associated with quality indicators of cancer care: receipt of comprehensive care, follow-up care instructions, and written treatment summaries. Less than two-thirds of participants reported shared care during their cancer treatment. The odds of reporting shared care were 2.5 (95% CI: 1.46–4.17) times higher for colorectal than breast cancer patients and 52% (95% CI: 0.24–0.95) lower for uninsured compared with privately insured, after adjusting for other sociodemographic, clinical/tumor, and health system factors. No significant relationships were observed between shared care and quality indicators of cancer care. Given a substantial proportion of patients did not receive shared care, there may be missed opportunities for integrating primary care and nononcology specialists in cancer care, who can play critical roles in care coordination and managing comorbidities during cancer treatment.